2014
DOI: 10.1038/bjc.2014.143
|View full text |Cite
|
Sign up to set email alerts
|

Histological grade concordance between diagnostic core biopsy and corresponding surgical specimen in HR-positive/HER2-negative breast carcinoma

Abstract: Background:The identification and validation of suitable predictive and prognostic factors are a challenge to improve the treatment scheme selection. Discordances in histological grade can be established between core biopsy and surgical specimens. This is important in HR-positive/HER2-negative subgroup where histological grade identifies patients at high risk and is a strong determinant for treatment scheme.Methods:A total of 350 consecutive invasive breast carcinoma biopsies were assessed and compared with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 29 publications
1
33
3
2
Order By: Relevance
“…However, the direct association between agreement and total core length was not analysed . Two other studies did not find an association of core biopsy length and grade concordance in CNBs versus SEBs, but in one study only the nuclear grade, not the Nottingham grade, was taken into account, and one analysed only minimum and maximum lengths of the cores, and not the total core length per biopsy set …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direct association between agreement and total core length was not analysed . Two other studies did not find an association of core biopsy length and grade concordance in CNBs versus SEBs, but in one study only the nuclear grade, not the Nottingham grade, was taken into account, and one analysed only minimum and maximum lengths of the cores, and not the total core length per biopsy set …”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have suggested that increasing the amount of biopsy material could improve the concordance of grade between CNBs and SEBs, the available data are inconsistent and sparse. One study reported improved grade agreement with increasing number of cores, whereas others failed to show an association between the amount of CNB material and grade agreement between CNBs and SEBs …”
Section: Introductionmentioning
confidence: 99%
“…Mitosis grades from core biopsies tend to be underestimated compared with from full tumour specimens, due to the small sample size of core biopsies and the intratumoral heterogeneity of breast cancer [34]. Therefore, in vivo, non-invasive measurement of conductivity via MREPT may provide information about mitosis Contrary to tumours ≥2 cm, tumours 1-2 cm in size with high mitosis grades or high Ki-67 values had lower conductivity without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…2a,b). Entsprechend ist die Konkordanz des Grades in präoperativen Biopsien vs. korrespondierenden Resektaten auch unabhängig von Größe und Anzahl der Biopsiezylinder [33]. Gelegentlich wird über eine Unterschätzung des histologischen Grades in Stanzbiopsien berichtet [33].…”
Section: Histologische Tumortypen Und Besondere Befundkonstellationenunclassified
“…Entsprechend ist die Konkordanz des Grades in präoperativen Biopsien vs. korrespondierenden Resektaten auch unabhängig von Größe und Anzahl der Biopsiezylinder [33]. Gelegentlich wird über eine Unterschätzung des histologischen Grades in Stanzbiopsien berichtet [33]. Ein Grund hierfür kann in der nicht ausreichenden Reprä-sentanz von Mitosefiguren bestehen; die Anwendung von Ki-67 an Stanzbiopsien kann den Anteil der falsch-niedrigen Grade reduzieren [34].…”
Section: Histologische Tumortypen Und Besondere Befundkonstellationenunclassified